2009
DOI: 10.1007/s11665-009-9562-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Surface Treating and High-Temperature Aging on the Strength and SCC Susceptibility of 7075 Aluminum Alloy

Abstract: A novel heat-treatment procedure combining the shot-peening with a two-step aging operation was proposed to improve both the strength and the stress corrosion cracking (SCC) resistance of the high-strength 7075 aluminium alloy. The heat treatment included one shot-peening stage before or between the two stages of aging at 120°C for 24 h and at 160°C for 1 h, respectively. The mechanical properties obtained during the aforementioned operations were extremely similar to those of the T6 sample owing to the unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…No stress-corrosion crack occurrence was noticed for the base metal and the time to failure in 0.6 M NaCl solution is even longer compared to the value measured at air. The role of active corrosion in NaCl solution can be hypothesized to enhance dislocation mobility and thus the plastic deformation, as reported by Jones et al [28,29]. The authors named this phenomenon anodic attenuation of strain hardening.…”
Section: Slow Strain-rate (Ssr) Testsmentioning
confidence: 84%
“…No stress-corrosion crack occurrence was noticed for the base metal and the time to failure in 0.6 M NaCl solution is even longer compared to the value measured at air. The role of active corrosion in NaCl solution can be hypothesized to enhance dislocation mobility and thus the plastic deformation, as reported by Jones et al [28,29]. The authors named this phenomenon anodic attenuation of strain hardening.…”
Section: Slow Strain-rate (Ssr) Testsmentioning
confidence: 84%
“…One of the main obstacles concerning the precipitation hardening (T6) of 7000 aluminum alloys, is decreasing the stress corrosion cracking (SCC) resistance of the alloy. 21 To increase the mechanical strength of the alloy and at the same time maintain the SCC resistance of the alloy, Fooladfar et al, 22 made use of shot-peening before conducting T6 heat treatment. One of the affecting items on the SCC is the size and the distance between the grain boundary precipitates (GBP) and it is stated that increasing the size and distance between GBPs, in other words, over-aging the GBPs is the remedy for SCC being decreased after T6.…”
Section: Literature and Discussionmentioning
confidence: 99%
“…It seems that, shot-peening besides all well-known effects, because of the plastic deformation it causes, may have the ability to overage the GBPs of the surface of the part after precipitation treatment. To verify this, Fooladfar 22 applied the explained procedure to the 7075 aluminum alloy and investigated the effects on the SCC behavior as well as the mechanical behavior of the alloy. Their study revealed that, shot peened then T6 heat treated alloy has both less SCC susceptibility and the same mechanical properties as T6 alloy.…”
Section: Literature and Discussionmentioning
confidence: 99%
“…However, over-aged tempers (e.g., T7, T73, and T76) generally have more resistance to SCC at the expense of a 10-15% decrease in the tensile strength compared with the peak-aged (T6) temper (Ref 9,10). Therefore, in order to optimize the strength and the resistance to SCC of the alloys, many efforts have been made to produce proper alloy microstructure in terms of the size and distribution of matrix strengthening and grain boundary precipitates as well, by adapting suitable solution heat treatment and artificial aging treatments ( Ref 11,12).…”
Section: Introductionmentioning
confidence: 99%